The Relationship Between Socioemotional Strengths and Self-Stigma Experiences of Youth with ADHD and their Parents. - Jelinkova, Kristina; Charabin, Emma; Miller, Courtney; Siemens, Theresa; Bath, Alexandra C.; Climie, Emma A. (Child Psychiatry & Human Development, 2026)
Attention-deficit/hyperactivity disorder (ADHD) is a neurodevelopmental disorder often associated with stigmatization, both from others and internally through self-stigma. This study explored how self-stigma relates to perceptions of socioemotional strengths in youth with ADHD and their parents. A total of 44 youth-parent dyads participated, completing strength-based and self-stigma measures. Hierarchical multiple regressions were conducted to determine the relation between youth or parent self-stigma and the perceptions of youth strengths. Partial correlations were used to examine associations between self-stigma and specific strength domains. Results indicated that higher youth self-stigma was significantly associated with lower self-rated strengths across all socioemotional domains, while higher parent self-stigma was linked to lower parent-rated strengths in family involvement and intrapersonal areas. Notably, youth self-stigma did not predict parent-rated strengths, and vice versa, suggesting self-stigma biases perceptions rather than reflecting objective differences in strengths. These findings highlight the potential negative impact of self-stigma on self- and parent-perceptions of youth capabilities and underscore the importance of interventions that target stigma reduction and promote strength-based perspectives. Future research should explore causality and the potential buffering role of strengths against the harmful effects of self-stigma.